Eight Needs of Every Partner, Parent, and Child - Victor William Harris (EDIS, 2012)
One of our greatest desires is to be happy. So, what do you need in order to be happy? Have you ever sat down and made a list? This 3-page fact sheet guides you in listing needs for yourself, your partner, and your children; and lists eight needs identified by researchers that people need to feel happy. Written by Victor William Harris and published by the UF Department of Family, Youth and Community Sciences, January 2012.